Improving Students’ Critical Thinking Ability in Exposition Text Through E-Writing - Dedeh Rohayati; Lilies Youlia Friatin (Yayasan Karinosseff Muda Indonesia, 2021)
The high increase of electronic media supported by internet resulted in accessing all information easily. Concurrently, the requirement of thinking critically intrigued all parties to be involved in the internet environment. This research aimed at investigating whether or not there were significant mean differences of critical thinking ability in writing exposition text between students who were taught by using E-writing method and those who were given traditional method of writing. The study employed quantitative paradigm design with the type of quasi experimental and involved students which was selected purposively and formed into experimental group and control group. The primary data was the result of pre-test and post-test in the form of essays which were scored by the Holistic Critical Thinking Scoring Rubric (HTCR) developed by Facione & Facione (2011). Based on the result of pre-test and post-test, NGain was analyzed through Man Whitney test to find out the significant mean different of students’ critical thinking ability. After being analyzed by using SPSS 23, the Mann Whitney test came up with the accepted hypotheses i.e., there were significant mean differences of critical thinking ability between experiment group and control group, with mean of NGain score for experimental group was higher than control group had. The statistical output of Mann Whitney test obtained implied that students’ critical thinking ability were influenced by E-writing method. The result of the study convinced that E-writing contributed greater improvement in students’ critical thinking ability than the traditional method did. The finding of present study provided evidence for the effectiveness of E-writing in increasing the students’ ability in thinking critically in writing exposition text.